Teaching Socio-Emotional Competencies Among Primary School Students: Improving Conflict Resolution and Promoting Democratic Co-existence in Schools - Santamaría-Villar, María B.; Gilar-Corbi, Raquel; Pozo-Rico, Teresa; Castejón, Juan L. (Frontiers in Psychology, 2021)
Teaching socio-emotional skills among primary school students is the key to creating a climate of cooperation in classrooms and reducing disruptive or aggressive behaviours among students. The primary goal of this research is to present an educational proposal for imparting socio-emotional competencies among primary school students. We attempt to impart socio-emotional competencies based on: 1) fostering self-knowledge, self-esteem, and respect for others among students; 2) developing behaviours that allow them to perceive and express feelings and self-regulating emotions; and 3) developing assertive communication skills aimed at improving conflict resolution. This program has been designed in such a way that it is implemented throughout the academic year by organizing bi-monthly sessions of forty-five minutes each, held until the completion of fifteen sessions. The sample consists of 100 students in the third grade, with the control and experimental groups having an equal number of students (50 each). The instruments used for this research are: a) BarOn Emotional Quotient Inventory (Youth Version [BarOn EQ-i:YV]): used for measuring emotional and social functioning; b) the Matson Evaluation of Social Skills with Youngsters (MESSY): used for assessing social skills; and c) Questionnaire for the Assessment of School Violence in Preschool and Primary School Questionnaire. To check the effectiveness of the educational intervention, a quasi-experimental design, along with pretest-posttest control group design, is used in accordance with the general linear model. Its effectiveness is also checked using repeated measures analysis of variance. The results show that the program is useful in preventing violent behaviours in the educational field and promoting the development of socio-emotional skills among third grade students. Finally, the applicability of the program to other educational contexts is discussed to enhance students’ personal development and decrease the levels of violence found in primary school.